Planning for the installation and rollout of WebSphere Studio Application Monitor 3.1 - Khimani, Bina (IBM redbooks., 2005)
This IBM Redbooks publication was written for anyone interested in the installation of WebSphere Studio Application Monitor (WSAM) for Multiplatforms including performance analysts, WebSphere administrators, and technical management. Our goal is to provide a useful overview and positioning of WSAM, and more importantly, an overview of the planning required for a WebSphere Studio Application Monitor installation. We also include hints, tips, and other pragmatic "how-to" information to help you install the product and be productive quickly and easily. However, in this book we point out those areas that customers tend to have questions about regarding installation and configuration, and offer suggestions based on our own experience. We also provide a "first place to look" for information on WSAM installation, with pointers to additional documentation and sources for those areas we cannot cover in depth. The book covers WSAM overview, pre-installation planning, care and feeding of WSAM, WSAM installation rollout planning, troubleshooting, firewalls, and ports.